The effect of walnut (tetracarpidium conophorum) leaf and onion (allium cepa) bulb residues on the tissue bacteriological changes of clarias gariepinus juveniles (2012)
In this study, the effect of walnut leaf (WL) and onion bulb (OB) residues on tissue bacteriology of Clarias gariepinus juveniles by dietary intake was investigated. Nine experimental diets: control (0%), OB2 (0.5%), OB3 (1.0%), OB4 (1.5%), OB5 (2.0%), WL6 (0.5%), WL7 (1.0%), WL8 (1.5%) and WL9 (2.0%) were formulated and replicated thrice at 40% crude protein. Fish (mean weight 7.4±0.02g) were fed twice daily at 3% body weight for 12 weeks. Microbiological analyses of water and fish (skin, gill, intestine and liver) and organ index (liver, spleen, kidney and heart) were investigated. Data were analysed using descriptive statistics and ANOVA at p=0.05. Results of enterobacteriacea and total viable count from this study revealed that bacterial loads on the water and fish of the experimental tanks were more affected by A. cepa and T. conophorum than the control for 4, 8 and 12 weeks and were significantly different (P<0.05) from the control. The values decreased in treated groups as the levels of inclusion (0.5%, 1.0%, 1.5% and 2.0%) increased and as the months increased. Also, organ index showed that the liver, heart, kidney and spleen were not significantly increased in all the treated groups and the control. The results suggest that walnut leaf and onion bulb residues inclusion in the diet of Clarias gariepinus could be a potential, less expensive and promising dietary supplementation that would positively influence growth, reduce and prevent bacterial infections in fish culture.